Intracardiac ablation for atrioventricular nodal reentry tachycardia using a 6 mm distal electrode cryoablation catheter: Prospective, multicenter, North American study (ICY‐AVNRT STUDY). (10th November 2017) - Wells, Peter; Dubuc, Marc; Klein, George J.; Dan, Dan; Roux, Jean‐Francois; Lockwood, Evan; Sturmer, Marcio; Dunbar, David; Novak, Paul; Rao, Arun; Peterson, Brett J.; Kueffer, Fred; et al.
Abstract: Introduction: Radiofrequency (RF) ablation is effective for slow pathway ablation, but carries a risk of inadvertent AV block requiring permanent pacing. By comparison, cryoablation with a 4‐mm distal electrode catheter has not been reported to cause permanent AV block but has been shown to be less effective than RF ablation. We sought to define the safety and efficacy of a 6‐mm distal electrode cryoablation catheter for slow pathway ablation in patients with atrioventricular nodal reentry tachycardia (AVNRT). Methods and results: Twenty‐six U.S. and eight Canadian centers participated in the study. Patients with supraventricular tachycardia (SVT) thought likely to be AVNRT were enrolled. If AVNRT was inducible and confirmed to be the clinical SVT, then the slow pathway was targeted with a cryoablation catheter using a standardized protocol of best practices. Acute success was defined as inducibility of no more than one echo beat after cryoablation. Primary efficacy was defined as acute success and the absence of documented recurrent AVNRT over 6 months of follow‐up. Primary safety was a composite of serious procedure‐related adverse events and/or device‐related complications. Note that 397 subjects met enrollment criteria after the EP study and received cryoablation. Mean ablation procedure duration (including a waiting period) was 89 ± 40 minutes, and mean fluoroscopy time was 4.8 ± 5.9 minutes. Isoproterenol was administered before cryoablation in 53% and after the last lesion in 85% of cases. Acute procedural success was realized in 95% (378 of 397) of subjects. No subject received a permanent pacemaker due to AV block. The slow pathway could not be ablated in 19 subjects, including: 12 due to inefficacy, 2 due to transient AV block, and 5 due to both inefficacy and transient AV block. RF ablation was used in the same procedure in 11 of 19 failed subjects, and was ineffective in 3 subjects. Among the group with acute success, 10 subjects (2.7%) had documented recurrent AVNRT over the 6‐month follow‐up period, and all occurred within 3 months of the index cryoablation. Serious procedure‐related adverse events occurred in 4 subjects (1.0%), including one each: tamponade, pulmonary embolism, femoral vein hemorrhage, and diagnostic EP catheter knotting. None of these serious adverse events were related to use of the cryoablation catheter. Overall, 93% of subjects had successful slow pathway ablation at 6 months with the study cryoablation catheter. Conclusions: Cryoablation for AVNRT using a focal 6‐mm catheter was safe and effective. It resulted in a low risk of recurrence over 6 months of follow‐up with no incidence of AV block requiring permanent pacing.